Green commercial property development in urban South Africa: emerging trends, emerging geographies - Rogerson, Jayne M. (Bulletin of Geography. Socio-economic Series, 2014)
Within sub-Saharan Africa South Africa is one of the leaders in greening and initiatives for sustainable urban development. Notwithstanding the central role of climate change impacts and of the green challenge for the future, the greening of urban development has not been a major focus in local geographical research. The task in this paper is to investigate one aspect of reorienting the economy towards a pathway of low carbon growth and of addressing the green urban challenge. Specifically, issues around the greening of commercial property developments in South Africa are explored. Under the ratings of the Green Building Council of South Africa 50 green buildings existed by early 2014. Geographically these properties cluster in South Africa’s major cities, in particular Johannesburg, the country’s economic powerhouse and centre for corporate headquarters, and Pretoria, the administrative capital. New proposals for building retrofitting may result in a greater spatial spread of green buildings in the near future.